Availability of Compliance Status in the Documentary Credit Opening Contract: A Study on the Jordanian Legislations - Al Maamari, Abdulwahab Abdullah; Al Ghuwairi, Abdallah Hameed (Mediterranean Journal of Social Sciences, 2021)
The letter of credit (L/C) contract is one of a range of banking operations through which banks can finance foreign trade. The contract provides security and stability to the trade because of the trust and credit it gives, since the buyer may be in one country and the seller in another, so as to assure each other that the other party fulfills its obligation. However, is this contract can be considered as a compliance contract so the relations between parties is a submissive weak-strong relationship? This necessarily entails examining the availability of legal protection to prevent the abuse of a strong party. Hence, this paper aims to examine the availability of compliance status in the documentary credit opening contract and focuses on the Jordanian legislations as a case study. The comparative analytical approach is executed in this study. The findings reveal that the L/C contract is influenced by the concept of compliance, however the L/C contract can be adjusted by the client, in accordance with the rules and provisions of this credit. Received: 31 January 2021 / Accepted: 27 February 2021 / Published: 7 March 2021